Examining the Dissertation in Practice Relative to RCR Responsible Conduct of Research - Carla J. Thompson (Impacting Education, 2023)
This essay focuses on the components and uses of the Dissertation in Practice (DiP) relative to the Carnegie Project on the Education Doctorate (CPED) and the alignment of the DiP description and process to the U. S. Office of Research Integrity Responsible Conduct of Research (RCR) conditions and requirements. The essay provides a cursory view of the multiple uses of applied research, a common framing of the DiP, and the essay examines the purpose and components of the DiP relative to the specific RCR criteria and specifications. Information provided explores the alignment of the DiP to RCR through discussions of the commonalities and diverse characteristics of the DiP and RCR to discern if these two important considerations regarding the framing of the Education Doctorate are a mismatch or an alignment. The potential for aligning the DiP with RCR may contribute substantially to propelling the DiP to the highest standard for inclusion within the listing of scholarly research.